2021
DOI: 10.1097/olq.0000000000001478
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Awareness of Hepatitis C Virus Among US Adults: An Analysis of the 2019 Health Information National Trends Survey

Abstract: Background: The U.S. Preventive Services Task Force updated hepatitis C virus (HCV) screening 2020 guidelines to target adults aged 18 to 79 years: a major shift from the prior focus on high-risk populations ("baby boomers" aged ≥55 years as of 2019). To inform efforts to maximize HCV screening coverage, our objective was to identify demographic groups reporting a lack of HCV awareness, particularly by race/ethnicity and age, and sources of health information. Methods:We used nationally representative data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This is important since inadequate knowledge about cirrhosis and HCC is considered a critical factor in awareness concerning attitudes toward prevention, HBV vaccination and testing, HCV screening and viral hepatitis treatment, 14 which may impact the Brazilian viral hepatitis elimination plan in the near future. 7 In this regard, knowledge about transmission, natural history and consequences of HCV 15 , 16 , 17 and HBV 17 , 18 , 19 , 20 infection in the general population from different parts of the world was reported to be inadequate even in hyperendemic areas of hepatitis B in Asia. 18 , 19 , 20 Due to its indolent course and lack of knowledge, many HBV- and HCV-positive patients were shown not to have confirmation of active infection or treatment to achieve sustained virological response, 21 , 22 many of them with advanced fibrosis or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important since inadequate knowledge about cirrhosis and HCC is considered a critical factor in awareness concerning attitudes toward prevention, HBV vaccination and testing, HCV screening and viral hepatitis treatment, 14 which may impact the Brazilian viral hepatitis elimination plan in the near future. 7 In this regard, knowledge about transmission, natural history and consequences of HCV 15 , 16 , 17 and HBV 17 , 18 , 19 , 20 infection in the general population from different parts of the world was reported to be inadequate even in hyperendemic areas of hepatitis B in Asia. 18 , 19 , 20 Due to its indolent course and lack of knowledge, many HBV- and HCV-positive patients were shown not to have confirmation of active infection or treatment to achieve sustained virological response, 21 , 22 many of them with advanced fibrosis or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Education level and/or income were significantly associated not only to attitudes toward HBV vaccination but also toward HBV and HCV testing and evaluation of liver health, which may be related not only to better access to healthcare but also to increased awareness and health literacy as previously highlighted by other reports. 17 , 29 Overall, 41%–48% of the Brazilians have performed either testing for viral hepatitis, liver enzymes or any diagnostic imaging test to assess liver health. The frequency of the Brazilian population already tested for HBV and HCV seems to be higher when compared to other populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data retrieved from social media about marginal communities can be very useful. For example, a survey in the US showed that awareness about hepatitis C virus is very low in a significant number of Hispanic and NH Asian young adults, who had never heard about HCV [191]. Authors of this study emphasized a social media campaign to educate targeted population about HCV screening.…”
Section: Current Status Of Viral Hepatitis and Digital Technologiesmentioning
confidence: 96%
“…Similar results were also observed in U.S. adults with low English fluency who were less aware of HCV. 18 Notably, up to 68% of participants with abnormal liver biochemistry and 69% of those with advanced fibrosis (FIB-4 > 3.25) still lacked disease awareness of their HCV infection.…”
Section: Relationship Between Hcv Diseases Awareness and Prevalencementioning
confidence: 99%